PENGARUH MARKETING MIX (4P) TERHADAP PENCAPAIAN TOP OF MIND DI ACE HARDWARE CABANG MAKASSAR - Syahril Ningki (Universitas Bina Taruna Gorontalo, 2024)
This research examines the influence of Marketing Mix (4P) on achieving top-of-mind awareness at Ace Hardware in Makassar. This study explores the impact of product, price, place, and promotional elements on consumer awareness and preference for Ace Hardware, particularly in the context of increasing competition in the retail industry for household appliances and equipment. This research combines comprehensive analysis including surveys and data to evaluate the effectiveness of Ace Hardware's marketing strategy and its impact on consumer decision making. The results of the research show that the implementation of Marketing Mix (4P) at PT Ace Hardware Indonesia, Tbk Makassar Branch. Partially, Product has a positive and significant effect, while Place, Price and Promotion do not have a positive or significant effect on Top of Mind by PT. ACE Hardware Makassar Branch. Simultaneously Marketing Mix (4P) has a positive and significant effect on Top Of Mind by PT. ACE Hardware Indonesia Makassar Branch, which means that when the Marketing Mix (4P) is implemented, the company's Top Of Mind will increase